Molecular cloning and partial characterization of unintegrated linear DNA from gibbon ape leukemia virus. - Scott, M L (1981)
We have cloned the complete genome of an oncogenic primate retrovirus, the San Francisco isolate of gibbon ape leukemia virus, in a lambda phage vector. DNA sequence analysis and restriction endonuclease mapping of the inserted linear provirus demonstrated 9-base pair inverted repeats at its ends, flanking direct terminal repeats 470 base pairs in length. The (-) strong stop region of this DNA showed surprisingly low sequence homology to that of another gibbon ape leukemia virus isolate from an animal with similar disease. Analysis of the clone also revealed the terminal phosphate configuration of the linear provirus. The recombinant phage is suitable for direct use as a hybridization probe to detect homologous retroviral sequences in human cell lines.